Perceived learning constructs and interaction patterns in a social networking site - Mohamad Said, Mohd Nihra Haruzuan; Yusup, Junaidah (2017)
This article reports on results of a study perceived learning constructs in a Social Networking Site (SNS) based on a two-round data collection from undergraduate Computer Science Education (CSE) studies.The first phase involved distribution of questionnaires to a total of 219 undergraduate students ranging from non-engineering (n=80) to engineering (n=139) that resulted in identification of three measured learning constructs: Social Bonding, Social Bridging and Social Intention.In phase two, evaluation of students’ learning transcripts in SNS were performed.Results identify 22 interaction patterns which then are further grouped into four learning dimensions of Participative, Interactive, Social and Cognitive.The findings indicated support for social connectivism, which promotes knowledge being distributed across a network of connections for each group of students.